(untitled) (Journal of the College of Education for Women, 2019)
The current research aims at studying the precise and big movement skills and the abilityof the diabetic child to do them, The research sample consisted of ten diabetic children whogo to the Diabetes Center of Research that is apart of the Yarmook hospital. The sample waschosen according to the intentional method and it wasn’t possible to have bigger samplebecause the parents of the children didn’t agree for fear on the children’s health. It wasapparent through the research that the diabetic child performs the big movement skills betterthan his ability to do the precise movement skills because they require accuracy,concentration and high attention.The most prominent recommendations and suggestions.1) The biabetic children have the ability to do the big movement better than doing the preciseones because they need concentration and high attention.2) The diabetic children show aloof ness and inactiveness in a clear way because of their lackof sugar.3) The children get diabetes as a result of heredity, obesity and facing direct accidents andagitations.4) The mother’s education and her academic attainments affect clearly in the possibility ofgetting diabetes.Recommendation:1) Doing periodic cheek up and especially for the children at the Kindergarten stage to detectanemia early.2) Taking care of the parent’s health, especially the mother prevents. Trans ferrying diabetesto the embryo during pregnancy and to have a healthy child.3) The necessity of taking care of the children’s nutrition especially at the early stage ofchildhood to prevent obesity.